ضبط احداثيات الموقع الجغرافي باستخدام نظام المعلومات الجغرافي - د. ايمن عبد الكريم الطعاني (My University, 2010)
This research aims at the identification of the geographic location coordinates on maps so that it is in conformity with nature. This is accomplished through the Arc View3.3 software, where the application process is illustrated step by step on images taken from applying Arc View3.3 and each step is numbered separately.
The process of controlling the geographic location coordinates is important when implementing geographical information system in research and scientific studies so the results are precise and correct.
The objectives of the research are as follows:
1. Illustrating the importance of controlling the geographic location coordinates.
2. Showing the sequence of steps of the identification (controlling) of coordinates.
3. Understanding the significance of geographical information system applications in studies and measurements and scientific research.

يقوم هذا البحث على التعريف الاحداثي للموقع الجغرافي على الخريطة بحيث يتم مطابقتة كما هو في الطبيعة ، ويكون ذلك بواسطة برمجية Arc View3.3 ،حيث تكون عملية التطبيق خطوه بخطوه بالصور المأخوذه من تطبيق برمجية Arc View3.3 وترقيم كل خطوه لوحدها، لان عملية ضبط احداثيات الموقع الجغرافي عملية لابد منها للذين يقومون بتطبيق نظام المعلومات الجغرافي في الابحاث والدراسات العلمية حتى تكون نتائج هذه الاعمال دقيقه وصحيحه .
من هنا تمثلت اهداف البحث بالاتي:
1. توضيح اهمية ضبط إحداثيات الموقع الجغرافي.
2. تسلسل عملية التعريف(الضبط) الاحداثي خطوه بخطوة.
3. ادراك اهمية نظام المعلومات الجغرافي في الدراسات والقياسات والابحاث العلمية.
ضبط احداثيات الموقع الجغرافي باستخدام نظام المعلومات الجغرافي